La «scientificità» della pedagogia ermeneutica - Riccardo Pagano (Studi sulla Formazione, 2010)
The author investigates the relationship between scientific pedagogy and hermeneutic pedagogy. Research has entered into the epistemology of human sciences and their different positions. The author begins with the well known duality between analytic and continental arguing that this opposition, despite being just and well founded, should be reread and reinterpreted to subtract the hermeneutic pedagogy from a state of weakness and immaturity. This short dissertation on the scientific dimension of pedagogy never loses sight of a paradigm now very important as the complexity.